Education Inequality in India: An Empirical Analysis Using National Sample Survey Data - MR, Aneesh; K, Maya; KA, Aneesh (Indian Journal of Human Development, 2024)
This research examines the rural-urban differences in educational inequality of major states in India. Using National Sample Survey Office (NSSO) data and decomposition methods, this study finds that overall educational inequality has come down but still very high in rural areas. We found that factors such as limited access to higher education, financial constraints and social factors are responsible for the high inequality in rural areas. This study highlights the need for government intervention to enhance educational access by increasing institutions and providing financial aid. It also notes that non-financial barriers like English proficiency further exclude lower socio-economic groups. Hence, we argue for inclusive education policies to improve the existing situation.
Keywords: Decomposition; Disparity; Gini Ratio; Inequality; Education